Microelectronics From Fundamentals to Applied Design - Di Paolo Emilio, Maurizio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book serves as a practical guide for practicing engineers who need to design analog circuits for microelectronics.  Readers will develop a comprehensive understanding of the basic techniques of analog modern electronic circuit design, discrete and integrated, application as sensors and control and data acquisition systems,and techniques of PCB design.  ·         Describes fundamentals of microelectronics design in an accessible manner; ·         Takes a problem-solving approach to the topic, offering a hands-on guide for practicing engineers; ·         Provides realistic examples to inspire a thorough understanding of system-level issues, before going into the detail of components and devices; ·         Uses a new approach and provides several skills that help engineers and designers retain key and advanced concepts.
1. Review of microelectronics -- 2. Bipolar Transistor -- 3. MOSFET -- 4. Operational Amplifier -- 5. Design PCB -- 6. Applications.
Keywords: Electronics; Electronic circuits; Electronics and Microelectronics, Instrumentation; Electronic Circuits and Systems